Structural Characterization and Anti-Gouty Nephropathy Potential of Polysaccharides from Atractylodes chinensis - Xue Chen; Ruipu Jia; Kai Zhang; Shiqing Sun; Mei Mei; Hong Zhao; Yu Shen; Yuliang Wang; Yu Zhang (Molecules)
Polysaccharides derived from Atractylodes chinensis (DC.) Koidz. (ACP), a traditional Chinese medicine, were extracted and analyzed for their structural characteristics and anti-gouty nephropathy (GN) activity. Sprague-Dawley (SD) rats were divided into six groups: control, model, positive control, and three treatment groups (ACP-60-L, ACP-60-M, and ACP-60-H). Treatment significantly reduced inflammatory responses and renal damage, as evidenced by decreased levels of uric acid (UA), creatinine (Cr), and blood urea nitrogen (BUN), alongside modulation of NOD-like receptor protein 3 (NLRP3) expression in renal tissues. ACP-60 was fractionated into three polysaccharides, including ACP-60-A (Mw 9.18 kDa), ACP-60-B (Mw 58.21 kDa), and ACP-60-C (Mw 109.01 kDa) using DEAE-52 cellulose column chromatography. Monosaccharide analysis revealed that ACP-60-A predominantly comprised fructose (Fru) and glucose (Glc), ACP-60-B contained rhamnose (Rha), galactose (Gal), Fru, and mannose (Man), and ACP-60-C included Man, Gal, Rha and xylose (Xyl). In vitro studies using HK-2 cells confirmed the anti-GN activity of all three fractions, with ACP-60-A demonstrating the highest efficacy. Structural elucidation of ACP-60-A identified its main glycosidic linkages as a →1)-β-Fruf-(2→ backbone with α-Glcp-(1→ and β-Fruf-(2→ branches. The underlying mechanism of ACP-60-A’s anti-GN activity is associated with inhibition of the NLRP3 inflammasome signaling pathway, suppression of downstream inflammatory factor release, and downregulation of NLRP3, ASC, and Caspase-1 protein expression. Further studies demonstrated that the superior activity of ACP-60-A is attributable to its lower molecular weight, specific monosaccharide composition, and unique glycosidic bond arrangement. ACP-60-A shows potential for increased anti-GN efficacy through purification or modification, laying the groundwork for developing novel therapeutic agents for GN.